Anomalies in Auction Choice Behavior - Radosveta Ivanova-Stenzel; Timothy C. Salmon (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
Ivanova-Stenzel and Salmon (2004a) established some interesting yet puzzling results regarding bidders' preferences between auction formats. The finding is that bidders strongly prefer the ascending to the first price sealed bid auction on a ceteris paribus basis but they are not willing to pay up to an entry price for entering into an ascending auction instead of a first price that would equalize the profits between the two. While it was found that risk aversion on the part of the bidders could resolve this anomaly the claim that risk aversion drives overbidding in first price auctions is somewhat controversial. In this study we examine two competing explanations for the observed behavior; loss aversion and 'clock aversion', i.e. a dislike for some aspect of the clock based bidding mechanism. We find that neither alternative explanation can account for bidders' auction choice behavior leaving risk aversion as the only un-falsified hypothesis.
urn:nbn:de:bvb:19-epub-13377-3
Keywords: C91; D44; 330; bidder preferences; private values; sealed bid auctions; ascending auctions